The use of sulphuric acid-carbonisation products of sugar beet pulp in Cr(VI) removal - Altundoğan, Hamdi Soner; Bahar, Nurdan; Müjde, Buket; Tümen, Fikret (My University, 2007)
A carbon rich adsorbent prepared from the reaction of sugar beet pulp with sulphuric acid and gas formed during carbonization process have been studied for Cr(VI) removal from aqueous solutions. The SO2 rich gas was shown to be an excellent Cr(VI) reductant. The equilibrium and kinetic studies were conducted by using the carbonaceous adsorbent derived from sugar beet pulp. The lower pH favoured Cr(VI) adsorption but substantial Cr(VI) reduction was observed. The Langmuir and Freundlich isotherm models were applied and the Langmuir model best fit the equilibrium isotherm data. The maximum adsorption capacity of chromium calculated from Langmuir isotherm is about 24 mg g?1 for 25 °C. The adsorption of Cr(VI) is an endothermic process and follows the pseudo-second-order rate kinetics. The sulphuric acid-carbonization is an economical method for particularly chromium removal because the gas generated during carbonization exhibits good Cr(VI) reduction properties and carbonaceous material obtained is an efficient Cr(VI) adsorbent.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sugar beet pulp; Carbonization; Activated carbon; Cr(VI) reduction; Cr(VI) adsorption; Heavy metal removal